Democratic ideals and levels of political participation: The role of political and social conceptualisations of democracy. (August 2018) - Oser, Jennifer; Hooghe, Marc
Concerns about democratic legitimacy in contemporary democracies bring new urgency to understanding how citizens' attitudes and ideals affect their political activity. In this article, we analyse the relationship between citizens' democratic ideals and political behaviour in the European Social Survey's 2012 uniquely extensive questions on these topics in 29 countries. Using latent class analysis, we identify two groups of citizens who emphasise different citizenship concepts as discussed by T.H. Marshall, namely, a political rights and a social rights conception. The multilevel regression analyses indicate that those who emphasise social rights have relatively high levels of non-institutionalised political participation, but are less involved in institutionalised participation. In contrast, those who emphasise political rights are more active in all forms of participation. We conclude by discussing the implications of the findings that, even in an era of economic austerity, those who emphasise social rights are not the most politically active.